Singing in an odd time: choir members’ perspectives on virtual choir experience and live choir experience - Ang, Mei Foong; Lok, Yew Chang; Tan, An Gie (Human Resource Management Academic Research Society, 2022)
The lockdown due to COVID-19 pandemic created big challenge to choir rehearsal and performance worldwide. Virtual choir has then emerged as a new global phenomenon where technology is used to reunite the choir members virtually during the lockdown. While virtual choirs had almost become the new standard for choir rehearsals and performances, it remained unknown if virtual choirs can provide an equal effective learning experience to the choir members. This study aimed to gauge the choir members’ overall experiences on both virtual rehearsal and performance, this study also aimed to find out the members’ selfreflection and satisfaction when redefining effectiveness in choir rehearsals as well as comparing the differences in terms of virtual experience reception between the universities’ choirs and the community choirs in Malaysia. A total of 112 participants in Malaysia were recruited through purposive sampling method where 83 (74.1%) were from the universities’ choirs and 29 (25.9%) participants came from the community choirs. Data were collected through online questionnaires on Google Form. Results demonstrated that choir members from both university choirs and community choirs faced similar challenges on virtual choir rehearsal and performances, whilst the community choir members are more tolerant and receptive of the virtual choir forms compared to the universities’ choir members.